Application of the marine ecosystem services approach in the development of the maritime spatial plan of Latvia. Issue 1 (1st January 2017) - Veidemane, Kristina; Ruskule, Anda; Strake, Solvita; Purina, Ingrida; Aigars, Juris; Sprukta, Sandra; Ustups, Didzis; Putnis, Ivars; Klepers, Andris
ABSTRACT: The Maritime Spatial Plan for Internal Waters, Territorial Waters and Economic Exclusive Zone of the Republic of Latvia is a long-term spatial planning document, which defines the permitted uses of the sea and conditions for development. Work on maritime spatial planning (MSP) in Latvia was a novel process from different aspects including incorporation of the concept of ecosystem services (ES) into MSP. In the course of the MSP process, marine ES were mapped and assessed, and impacts of proposed spatial solutions for the use of the sea were assessed. The scope of mapping and assessment of ES was limited by data availability and expert knowledge on marine ecosystems. MSP in Latvia was an open and transparent process with an active involvement of different stakeholder groups. Marine ES assessment results were visualized and used during the public consultations to highlight the marine areas providing the most significant social benefits as well as to facilitate debate about potential impacts arising from proposed uses of the sea. The marine ES approach, in a spatially explicit manner, provided stakeholders and policymakers with a strategic framework to address a complex social–ecological system.EDITED BY Joao Rodrigues